6x-12=9x+15

Simple and best practice solution for 6x-12=9x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-12=9x+15 equation:


Simplifying
6x + -12 = 9x + 15

Reorder the terms:
-12 + 6x = 9x + 15

Reorder the terms:
-12 + 6x = 15 + 9x

Solving
-12 + 6x = 15 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-12 + 6x + -9x = 15 + 9x + -9x

Combine like terms: 6x + -9x = -3x
-12 + -3x = 15 + 9x + -9x

Combine like terms: 9x + -9x = 0
-12 + -3x = 15 + 0
-12 + -3x = 15

Add '12' to each side of the equation.
-12 + 12 + -3x = 15 + 12

Combine like terms: -12 + 12 = 0
0 + -3x = 15 + 12
-3x = 15 + 12

Combine like terms: 15 + 12 = 27
-3x = 27

Divide each side by '-3'.
x = -9

Simplifying
x = -9

See similar equations:

| A=11x+kx | | 15x=13x+12 | | 4v=40 | | 10x+24=Xb+ax+ab | | log(6)(6x-1)=1 | | 3(2x+6)=4x-8 | | z=2z+3z | | 252=45t | | 0.15x+3.45=46.5 | | -2(4n+4)=6 | | H=35t-16t^2 | | -3y+8=9 | | 15*3n= | | -1/7t9 | | 5(5x-2)=15 | | 4-9/5x5 | | 1.5x=16 | | P=2(62)+2(65) | | 4x-2z=3y | | 5d-(-3)=53 | | 8x+7-y=38 | | y=9x^2+18*x-6 | | 5p+(3p-20)=180 | | 7=x/2-5 | | 5d-(-3)=52 | | -x-23=5x | | 93=16-5x | | (10x-4)(x+1)=0 | | -4(v-2)=-6n+34 | | 2(4w+10)*3=6 | | 3v+36=-6v | | 3ab+6ba= |

Equations solver categories